Exploration of the Impact of Transformational Leadership on Organizational Citizenship Behavior: The Mediation Role of Organizational Commitment - Tumpak Maniroy Sinaga; Aryana Satrya (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of Transformational Leadership on Organizational Citizenship Behavior, considering the mediating role of Organizational Commitment. The research method used is a quantitative approach, with a survey to collect data from employees of PT. ElectriCo. The sample consisted of 249 employees who were randomly selected but representative of each Division at PT. ElectriCo. The research approach in this study uses causal-predictive modeling with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The overall results of the hypothesis testing indicate that the data consistently support the model proposed in this study. The findings of this study indicate that Transformational Leadership has a direct positive effect on Organizational Commitment and Organizational Citizenship Behavior. The findings of this study also indicate that high Transformational Leadership will have a positive effect on Organizational Commitment, which will then increase Organizational Citizenship Behavior. Transformational Leadership also directly increases Organizational Citizenship Behavior.